044 Collegial Collaboration Managing Joint Projects Across Societies. (15th August 2013) - Fatheree, L; Wick, M; Larsen, S; Olsen, J
Abstract : Background: Pooling resources for the development and dissemination of guidelines receives important consideration due to the extensive amount of expertise, money and staff time needed within an organisation. Partnered guidelines may increase the administrative cost and timeline of development, but is positively offset in the value partnering brings in the ultimate success and implementation. Context: Over the last three years we formally partnered with other professional medical societies in over 70% of our guidelines, learning many core and nuanced components of a successful jointly-developed guideline. We share those lessons learned with GIN members. Description of Best Practice: We tackle critically important aspects of joint collaborations, beginning with the determination of appropriate partners. We explore the creation of a solid memorandum of understanding (MOU), addressing questions like: How will we select panel membership and manage their conflicts of interest? What grading system will we utilise with an evidence-based guideline or consensus conference? How will we approach our respective organisation's approval process? What is needed to produce a simultaneous joint publication between journals? How will we disseminate effectively to our target audiences? What is our future plan for a revision? And the ultimate questions - How do we cost share and work share in the development equally? Lessons for Guideline Developers, Adaptors, Implementers, and/or Users: These experiences will help guideline developers create a framework for partnered collaborations, balancing value gained in partnership versus challenges realised in completion and resourcing.